1991
DOI: 10.1111/j.1365-2605.1991.tb01099.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pentoxifylline on superoxide anion production by human sperm

Abstract: The in-vitro effect of pentoxifylline, a methylxanthine derivative, on superoxide anion generation by sperm was studied in 27 men with superoxide anion production ranging from 0.57 to 13.8 nmoles 02-. per 10(6) sperm. Superoxide anion release stimulated by phorbol myristate acetate, a potent activator of oxygen radical generation, was reduced by 29-72% following the addition of 10 mM pentoxifylline. The inhibitory effect of this millimolar concentration of the drug did not depend on the initial superoxide prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(31 citation statements)
references
References 18 publications
1
29
1
Order By: Relevance
“…Gavella et al 71 and Gavella and Lipovac 72 found that superoxide anion production was reduced by the addition of 10 mmol l 21 of pentoxifylline, as did McKinney et al 73 and Okada et al 74 in their respective studies, albeit with different doses. It should also be stressed that in McKinney's study, 73 reduced lipid peroxidation was observed after the addition of pentoxifylline (dosages from 3.6 to 7.2 mmol l 21 ), and that in Okada's study 74 doses from 1 to 10 mmol l 21 led to preserved motility, due to reduced loss of curvilinear velocity and beat-cross frequency.…”
Section: Pentoxyfillinementioning
confidence: 77%
See 1 more Smart Citation
“…Gavella et al 71 and Gavella and Lipovac 72 found that superoxide anion production was reduced by the addition of 10 mmol l 21 of pentoxifylline, as did McKinney et al 73 and Okada et al 74 in their respective studies, albeit with different doses. It should also be stressed that in McKinney's study, 73 reduced lipid peroxidation was observed after the addition of pentoxifylline (dosages from 3.6 to 7.2 mmol l 21 ), and that in Okada's study 74 doses from 1 to 10 mmol l 21 led to preserved motility, due to reduced loss of curvilinear velocity and beat-cross frequency.…”
Section: Pentoxyfillinementioning
confidence: 77%
“…It should also be stressed that in McKinney's study, 73 reduced lipid peroxidation was observed after the addition of pentoxifylline (dosages from 3.6 to 7.2 mmol l 21 ), and that in Okada's study 74 doses from 1 to 10 mmol l 21 led to preserved motility, due to reduced loss of curvilinear velocity and beat-cross frequency. [71][72][73][74] However, in 1998 Twigg et al 19 found no improvement in lipid peroxidation after the addition of 3.6 mmol l 21 of pentoxifylline.…”
Section: Pentoxyfillinementioning
confidence: 99%
“…The improvement of fertilisation may be caused by the antioxidant effect of pentoxifylline, as suggested by Gavella et al (1991). Moreover, Numabe et al (2001) found an increase in fertilisation, monospermy, cleavage and blastocyst rates after treating bull spermatozoa with pentoxifylline.…”
Section: Discussionmentioning
confidence: 90%
“…4,9 Recently, studies have focused on assessing the effectiveness of in vivo and in vitro supplementation with different antioxidants in an attempt to protect spermatozoa exposed to oxidative stress. [10][11][12][13][14] A beneficial effect of the in vitro supplementation of different natural or chemically synthesized antioxidant compounds on human spermatozoa has been observed; however, their effect has also been shown to decrease at inadequate concentrations and, even worse, to behave as pro-oxidants. 11,12,15,16 Herein, we discuss the protective role of exogenous gangliosides against ROS-induced changes based on our studies of human spermatozoa, leukocytes and cell-free systems.…”
Section: Introductionmentioning
confidence: 99%